Persianate selves - Kia, Mana. (Stanford, California)
xxiv, 312 sayfa
Keywords: “Persianate Selves challenges accepted notions of what it meant to be Persian in the eighteenth century. Drawing on commemorative texts, this book reveals that to be Persian was not necessarily to be Iranian. Persians hailed from a variety of places across Central, South, and West Asia, and their sense of self was not tied to modern ideas of nationalism, religion, or race. Mana Kia explores the common education and cultural logic that connected Persians, before the concept of the nation, describing how place, origin, and memory created a sense of self unbounded by the limits of colonial modernity“ --